Use of Ferric Chloride Zeolites in Ground Water Treatment at Household Level a Case Study of Kyabalogo Village, Nakisunga Sub-county - Ivan Joseph Lubulwa (Uganda Christian University, 2025)
The issue of access to clean drinking water continues to be a great struggle in various rural locations where the sources of groundwater are becoming more and more polluted with heavy metals and other inorganic substances. At the same time, heavy metals such as lead (Pb²⁺) and copper (Cu²⁺) are classified as hazards of the highest order due to their toxic nature, persistence, and bioaccumulation (Tchobanoglous et al., 2014). A study on water quality in Kyabalogo Village, Nakisunga Sub-county, Mukono District, Uganda, indicated the existence of Pb and Cu in the spring water exceeding the tolerable limits for drinking water. Therefore, the water cannot be used in households without prior Purification household level. The current work is focused on the application of natural zeolite as an inexpensive and effective adsorbent to purify the spring groundwater by removing Pb²⁺ and Cu²⁺ at the Previous literature shows that divalent heavy metals can be taken away by zeolites by 80–95% via ion-exchange processes, where the ions of the heavy metals Pb²⁺ and Cu²⁺ in the solution replace the cations (e.g., Na⁺, K⁺, Ca²⁺) that are in the zeolite lattice (Misaelides, 2011). The results of this research work are expected to provide a cheap and an eco-friendly approach solution for the rural water treatment community. (Wang & Peng, 2010).